Literatura polska w przekładach na język bułgarski. Czasopisma literackie w latach 1990—2007 / Bulgarian Translations of Polish Literature in the Periodical Literature, 1990—2007 - Bahneva, Kalina (Przekłady Literatur Słowiańskich, 2009)
This text examines the reception of Polish literature into professional Bulgarian publications for literature and art. It submits to a discussion the following sources: The special issue of „Literaturen westnik” („Literary Weekly”) entitled Polish Literature of the Nineties, no.11 (22.—28.03.2000), devoted entirely to the changes occurred in Polish literature and artistic life at the end of the past century; and no. 18 (8.—14.05.2002) of the same journal presents under the title Polish Nike, presents the most prestigious Polish literary award and its laureates during the years 1997—2002. Mentioned above journal „Literaturen westnik” („Literary Weekly”) had two more special issues: Literature on Heel – or Better Literature, no. 35 (2.—8.11), and Literature before the Mirror or Better Literature, no. 6 (15.—21.02), published in 2006, both focused on Polish women’s feminist writers. The article takes also into account the issue of „Panorama”, no. 3 (2002), which gives an overview of Polish literature translated into Bulgarian after 1989. Included into this discussion is the periodical „Kritika”, no. 3—4 (2006); it gives a survey of the most interesting statements of Polish literary critical thought in the same period, that is, after 1989. Similarly, the „Slavianski dialozi” („Slavic Dialogues”), no. 8 (2007), that presents some most important ways of development in contemporary Polish culture.